Dried and dehydrated fruit products for commercial markets - Gupta, Alok Kumar; Singh, Abha; Singh, Akath; Das, Swosti S; S C, Ravi (Indian Horticulture, 2026)
Subtropical fruits such as mango, guava, aonla, bael, and jamun encounter considerable post-harvest losses ranging from 20% to 30% due to high perishability. ICAR-CISH Lucknow has innovated novel products by using drying and dehydration methodologies, such as osmotic dehydration, freeze-drying, infrared drying, and microwave-assisted drying, to mitigate these losses. The application of these methods enhances shelf life, minimizes transportation expenses, and maintains both nutritional and sensory attributes. Products like freeze-dried fruit powders and cubes, leathers, candies, and pulp blocks/ cubes address the increasing domestic and international demand for nutritious and convenient snack options. The technologies developed by the institute, in conjunction with its Agri-Business Incubation program, facilitate the advancement of commercialization and promote rural entrepreneurship.